ALIRAN FILSAFAT EKSISTENSIALISME MARTIN HEIDEGGER DALAM PENDIDIKAN ISLAM - Munauwarah, Rahmadin; Arifi, Ahmad; Resmiyanto, Rachmad (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2023)
This article discusses the philosophical school of existentialism by a philosopher from the German city of Messkirch named Martin Heidegger. Existentialism focuses on the situation or existence of humans in the world. The emergence of existentialism began with the philosophers Soren Kierkeggard and Nietzsche. Not only is that the cause of its emergence but also as a form of resistance to respond to the assumptions provided by materialism and idealism regarding human existence. The type of research used is qualitative (library research) with an analysis model using analytical descriptive methods (critical analysis and critical interpretation). The aim of this research is firstly to find out the philosophy of existentialism in general, secondly to find out existentialism according to Martin Heidegger, and thirdly to find out the relationship between the philosophy of existentialism and Islamic education.